?m-Deferred Statistical Convergence of Order ? - Temizsu, Fatih; Et, Mikail; Cinar, Muhammed (Univ Nis, Fac Sci Math, 2016)
In this paper, we introduce the concepts of Delta(m)-deferred statistical convergence of order alpha and strong Delta(m)(r)-deferred Cesaro summability of order alpha of real sequences. Additionally, some inclusion relations about Delta(m)-deferred statistical convergence of order alpha and strong Delta(m)(r)-deferred Cesaro summability of order alpha are given.
2nd International Conference on Recent Advances in Pure and Applied Mathematics (ICRAPAM) -- JUN 03-06, 2015 -- Istanbul Commerce Univ, Fac Arts & Sci, Istanbul, TURKEY
Keywords: Delta(m)-deferred statistical convergence; strong Delta(m)-deferred Cesaro summability